Epidemiology of major reproductive health problems and associated infectious diseases in commercial and smallholder dairy herds in North Shewa, central highlands of Ethiopia - Aweke Engdawork; Haileleul Negussie; Awoke Melak (Frontiers in Veterinary Science)
IntroductionReproductive health problems are disorders of the reproductive system and are the most common cause of economic losses in the dairy industry. Despite the widespread occurrence of reproductive health problems and infectious diseases, their epidemiology is little known in Ethiopia.MethodsA cross-sectional study was conducted to identify major reproductive health problems, infectious reproductive diseases, and risk factors in commercial and smallholder dairy herds in North Shewa, central highlands of Ethiopia. Blood samples were collected from randomly selected 142 dairy herds and 511 animals and serologically examined with ELISA for IBR and CFT for brucellosis. Two years of retrospective data were collected to identify major reproductive problems in dairy herds.ResultsThis study indicated overall seroprevalence of IBR in 85.21% (95% CI: 78.28–90.21%) dairy herds, while bovine brucellosis was prevalent in 3.52% (95% CI: 1.46–8.26%) herds. The most prevalent reproductive problems in dairy herds were abortion (27.46%; 95% CI: 20.68–35.48), retained placenta (33.80%; 95% CI: 26.42–42.06), repeat breeding (40.14%; 95% CI: 32.32–48.50), anoestrus (37.32%; 95% CI: 29.68–45.66), and calf mortality (29.58%; 95% CI: 22.58–37.69). Herds infected with IBR were more at risk of abortion (OR = 8.34; 95% CI: 1.91–76.96; p = 0.006), retained placenta (OR = 8.61; 95% CI: 1.04–70.89; p = 0.045), repeat breeding (OR = 3.16; 95% CI: 1.82–12.23; p = 0.009), anoestrus (OR = 6.63; 95% CI: 1.28–34.38; p = 0.024), and calf mortality (OR = 4.05; 95% CI: 1.81–20.32; p = 0.008). Brucellosis exposure increased abortion by 21 (p = 0.037), retained placenta by 19 (p = 0.003), and anoestrus by 12 (p = 0.002) times. Herd size and breeding methods were significantly associated with abortion, repeat breeding and calf mortality; while replacement strategies and bull-sharing were significant factors of retained placenta and anoestrus (p < 0.05).ConclusionThis study demonstrates higher occurrences of reproductive problems and circulating infectious diseases in commercial and smallholder dairy herds. Thus, integrated disease control measures such as vaccination, biosecurity, herd screening, and sound management should be practiced to control reproductive health problems and promote the growing dairy production in North Shewa in the central highlands of Ethiopia.